The prognostic significance of stress hyperglycemic ratio in critically Ill patients with hypertension: A study using the MIMIC-IV database - Zirong Li; Yufei Wu; Qian Jin; Taiwei Lou; Yi Kang; Xianbei Wang; Ning Sun; Tian Ni; Zhengchuan Zhu; Miaoran Wang; Qiuyan Li (PLoS ONE, 2026)
Background Traditional ABG is susceptible to interference from acute stress and daily fluctuations, making it difficult to accurately assess true acute blood glucose surges. To bridge this gap, we adopted the Stress Hyperglycemia Ratio (SHR), which reflects true acute hyperglycemia by controlling for baseline glucose status. SHR is associated with critical illness and has been shown to associated with in-hospital mortality. However, there is a lack of studies investigating SHR and its prognostic significance in patients with hypertension. Methods This study utilized the Medical Information Mart for Intensive Care IV database (MIMIC-IV) to extract patient information. All subjects were divided into four groups based on the quartiles of SHR. Kaplan-Meier (KM) curves were utilized to assess the relationship between SHR and all-cause mortality at 30, 90, 180, and 365 days. The relationship between the SHR index and prognosis was evaluated using restricted cubic spline (RCS) regression and Cox proportional hazards regression. At the same time, subgroup analyses were performed for gender, age, diabetes, myocardial infarction, congestive heart failure, cerebrovascular disease, and paraplegia. Results A total of 2,140 participants with essential hypertension were included in the study. The KM curve analysis revealed that elevated levels of the SHR index were significantly associated with an increased risk of all-cause mortality at 30, 90, 180, and 365 days (log-rank P < 0.05). Moreover, multivariate analysis revealed that the SHR index remained significantly associated with mortality risk ( P < 0.001 ) . RCS analysis revealed a nonlinear, inverse U-shaped association between SHR and all-cause mortality ( P < 0.05). Subgroup analysis showed statistically significant differences in all-cause mortality across gender, age, diabetes, myocardial infarction, heart failure, cerebrovascular disease, and paraplegia. Conclusions In critically ill patients with hypertension, a high level of SHR index is associated with all-cause mortality. The SHR index may be a potential prognostic indicator for assessing illness severity in ICU patients with hypertension.